Implications of Vitamin D in Multiple Sclerosis and Other Neurodegenerative Processes: Bibliometric Analysis and Systematic Review - Caballero-Villarraso, Javier; Jiménez-Jiménez, María J.; Escribano, Begoña M.; Agüera, Eduardo; Santamaría, Abel; Túnez, Isaac (CNS & Neurological Disorders - Drug Targets, 2019)
In recent years, numerous investigations focused on the pleiotropic actions of vitamin D have been carried out. These actions include the participation of this molecule in neurophysiological and neuropathological processes. As a consequence, abundant scientific literature on the role of this vitamin in neurodegenerative entities has emerged, even concerning clinical studies. To identify the level of scientific evidence concerning the relation between vitamin D and neurodegenerative diseases, from a quantitative and qualitative perspective. To describe, by means of a bibliometric analysis, the scientific production and its evolution through time in quantitative terms, regarding the implications of vitamin D in neurodegeneration. To analyse and present the degree of evidence in the aforementioned field of study, a systematic review of the literature focused on the most prevalent neurodegenerative diseases was carried out. We retrieved 848 articles in the bibliometric analysis, the majority of which were dated between the years 2010-2017. The most studied metabolite was the 25(OH)D3 and the most cited disease was multiple sclerosis. In the systematic review, we found studies about Alzheimer’s and Parkinson’s diseases and again, about multiple sclerosis prominently (in number and quality), with 12 randomised double-blind clinical trials. The research about vitamin D and its relations with neurodegenerative diseases shows a growing evolution over the last decade. More studies are needed to find correlations between the clinical severity of these diseases and the specific status of vitamin D and the genotypes related with them, which seems to be a future trend.
Keywords: multiple sclerosis